Design and performance of bioreactor for fermentative biogas production from marine microalgae. (February 2019) - Abobaker, M S A; Anggunsari, R; Nurlailati, S; Susilo, B; Dewi, S R; Wibisono, Y
Abstract: Novel application of marine microalgae as a new source of renewable energy production, by using anaerobic digestion route, is presented in this paper. Traditionally, biogas was produced from animal manure. Microalgae however, has a potential application to be fermented and converted into biogas. This work describes the design of bioreactor to produce biogas. The bioreactor was made of stainless steel tube of 250 ml with a thickness of 2 inches, and surrounded by a water jacket with the height of 10 cm, diameter of 8 cm. The temperaure was controlled using thermocouple and data logger. The bioreactor contains stirring system to maintain good mixing. On the top side, a hose is used as biogas outlet and the gas pressure was measure. Testing of bioreactor was done using Dunaliella salina microalgae as main subtrate and tofu wastewater as additional subtrate. The anaerobic digestion was maintained from 7, 14 and 21 days, and the biogas produced were collected. The methane content analyzed by using gas chromatography and despite its low methane prodcution, it is found that microalgae is potentially used as biogas feed.